Efficient hydrogenation of biomass derived cyclic di-esters to 1,2-diols - Balaraman, Ekambaram; Fogler, Eran; Milstein, David (Chemical Communications, 2012)
The unprecedented homogeneous hydrogenation of cyclic di-esters, in particular biomass-derived glycolide and lactide, to the corresponding 1,2-diols is catalyzed by Ru(II) PNN (1) and Ru(II) CNN (2) pincer complexes under mild hydrogen pressure and (in the case of 1) neutral conditions. No racemization was observed when a chiral di-ester was used.